Evaluation in Assessment of Student Competence: Application of the Indonesian Student Competency Assessment (AKSI) in Elementary Schools - Mustari S. Lamada; Sanatang Sanatang; Aulyah Zakilah Ifani; Dwi Hastuti Hidayat (International Journal of Environment, Engineering and Education, 2022)
The purpose of the study was to determine the application of the Indonesian Student Competency Assessment application at the elementary school level, to determine the readiness of teachers, to find out the ease of guidance and the suitability of literacy and numeracy learning modules with assessment questions, and to find out the obstacles experienced by teachers during the process of using the Application of Indonesian Student Competency Assessment (AKSI) application using a purposive sampling technique. Data collection using questionnaires and documentation. Data analysis in this study used descriptive statistics. The results showed that the application of the Indonesian Student Competency Assessment application at the elementary school level in, Takalar Regency had been implemented well. Research with sub-variables of the application of the Indonesian Student Competency Assessment application at three elementary schools for students obtained data showing 44.70% were in a good category. The readiness of teachers to apply the AKSI application obtained data that 84.80% were in the ready and very ready category and the very ready category was balanced with the ready category. The ease of guidance and the suitability of the literacy and numeracy learning modules with the assessment questions provided by the AKSI application for teachers obtained data that showed 39.00% were in the very good category. Obstacles experienced by teachers during the process of using the AKSI application, data showed that 35.70% were in the high category